Perencanaan Pembangkit Listrik Tenaga Surya Sebagai Suplai Energi Listrik Pada Musholla Baitul ‘Ilmi Kota Padang - Arjuna Pamungkas Chan; Rosnita Rauf; Budiman Budiman (Journal of Innovative and Creativity, 2025)
ABSTRACT This study aims to analyze the technical and economic feasibility of an on-grid Solar Photovoltaic (PV) system for the Baitul Ilmi Musalla in Padang City. The total electrical load of the musalla reaches 2,047 watts, with a daily energy requirement of 7,283 Wh. The system was designed using four monocrystalline solar panels, each with a capacity of 450 Wp, resulting in a total installed capacity of 1,800 Wp across an array area of approximately 7.86 $\text{m}^2$. The selected inverter has a capacity of 2,500 watts, which is appropriate for the power requirements and maintains a necessary safety margin. Power degradation due to module temperature increase ($Δ T$) was estimated to be 11.05 watts. Based on simulation results, the system is capable of generating approximately 6.48 kWh of electricity per day, sufficient to support the musalla's daytime energy needs. The estimated total investment cost for the system is Rp16,850,000. Economic analysis results indicate that the system has a payback period of 3.79 years, equivalent to 3 years, 9 months, and 14 days. Thus, the implementation of an on-grid PV system in religious buildings like the musalla is deemed feasible and efficient for supporting the use of renewable energy. Keywords: On-grid PV, Solar Energy, Inverter, Monocrystalline Solar Panel ABSTRAK Penelitian ini bertujuan untuk menganalisis kelayakan teknis dan ekonomis sistem Pembangkit Listrik Tenaga Surya (PLTS) on-grid pada Mushalla Baitul Ilmi di Kota Padang. Beban listrik total mushalla mencapai 2.047 watt dengan kebutuhan energi harian sebesar 7.283 Wh. Sistem dirancang menggunakan empat panel surya monokristalin berkapasitas 450 Wp per unit, sehingga total kapasitas terpasang mencapai 1.800 Wp dengan luas array ±7,86 m². Inverter yang digunakan memiliki kapasitas 2.500 watt, sesuai dengan kebutuhan daya dan margin keamanan. Penurunan daya akibat kenaikan suhu modul (ΔT) diperkirakan mencapai 11,05 watt. Berdasarkan hasil simulasi, sistem mampu menghasilkan energi listrik sebesar ±6,48 kWh per hari, yang cukup untuk menopang kebutuhan siang hari. Estimasi total biaya investasi sebesar Rp16.850.000. Hasil analisis ekonomi menunjukkan bahwa sistem memiliki periode pengembalian investasi (payback period) selama 3,79 tahun atau setara dengan 3 tahun 9 bulan 14 hari. Dengan demikian, penerapan sistem PLTS on-grid pada bangunan ibadah seperti mushalla dinilai layak dan efisien dalam mendukung penggunaan energi terbarukan. Kata Kunci: PLTS on-grid, energi surya, inverter, panel surya monokristalin